Temperature dependent magnetization of the two band model for diluted magnetic semiconductors - Thai, Vu Kim; Tuan, Hoang Anh (Communications in Physics, 2014)
The temperature dependent magnetization of a two band model for diluted magnetic semiconductors as a function of magnetic coupling constant, hopping parameters and carrier densities is calculated by using the coherent potential approximation. It is shown that the degree of overlapping of the impurity bands and carrier density are crucial parameters determining the magnetization behavior of the system